An injectable particle-hydrogel hybrid system for glucose-regulatory insulin delivery. (December 2017) - Zhao, Fuli; Wu, Di; Yao, Dan; Guo, Ruiwei; Wang, Weiwei; Dong, Anjie; Kong, Deling; Zhang, Jianhua
Graphical abstract: Abstract: Long-term and daily subcutaneous injections of insulin for the treatment of insulin-dependent diabetic patients often lead to poor patient compliance and undesired complications. Phenylboronic acid (PBA)-based polymeric hydrogels have been widely considered as one of the most promising insulin delivery system to replace the frequent insulin injections. However, their applications are limited by clinically irrelevant glucose-responsive range, slow response rate, low tissue-adhesiveness and poor biodegradability, undesirable leakage at normoglycemic state. Herein, we report a novel implantable insulin hydrogel for glucose-regulated delivery of insulin based on a unique particle-hydrogel hybrid platform featuring fast glucose responsiveness at physiological pH, shear-thinning behavior for injection, tissue-adhesive function for long-lasting adherence, and full biodegradability for safe use. The system was thoroughly characterized both in vitro and in vivo and was demonstrated to hold these unique functions. Using streptozotocin-induced diabetic mice as a model, it was shown that a single subcutaneous injection of the insulin-loaded particle-hydrogel formulation led to quasi-steady-state blood glucose levels within the normal range for about two weeks. In addition, the preparation of the formulation only involved simple mixing and self-assembling processes, and thus it had great scalability and reproducibility for practical use. The highly feasible preparation, excellent performance, inherent biocompatibility and biodegradability make this novel composite hydrogel promising platform for diabetes therapy. Statement of Significance: Phenylboronic acid (PBA)-based polymeric hydrogels have been widely considered as one of the most promising insulin delivery system to replace the frequent insulin injections. However, these hydrogels, mostly based on a variety of PBA-containing acrylamide monomers, are still far from clinical reality. Building upon a unique particle-hydrogel hybrid platform, herein we report a novel implantable insulin storage and delivery system with multifunctionalities including fast glucose-sensitiveness at physiological pH, shear-thinning behavior for injection, tissue-adhesive function for long-lasting adherence, biodegradable materials for safe use and well-controlled insulin release. These unique functions were demonstrated through research both in vitro and in vivo . In addition, the preparation of the formulation was simple, and thus it had great scalability and reproducibility for practical use.